Lag Screw Design Is a Predictor for Cut-Out Complication After Intertrochanteric Femur Fracture Treatment in Elderly. A Comparative Analysis - Aytek Hüseyin Çeliksöz MD; Nusret Köse; Akın Turgut; Erol Gökturk (Geriatric Orthopaedic Surgery & Rehabilitation)
Background: Hip fractures are common in older adults and are associated with significant morbidity and mortality. Surgical fixation with intramedullary devices, such as proximal femoral nails (PFN), is a common treatment method. However, complications such as implant cut-out remain a challenge despite advancements in implant designs. The objective of this study was to evaluate the clinical experience with different PFN designs and lag screws and to compare implant cut-out rates. Additionally, the study aimed to identify the most important factors that could prevent complications and predict cut-out. Methods: This retrospective study included 145 patients with trochanteric fractures who had undergone surgical treatment with PFN devices between January 2015 and December 2018. Patients younger than 65 years, those with pathological fractures, ipsilateral pelvic and knee fractures, subtrochanteric fractures, and multiple traumas were excluded. Radiographs were evaluated to determine osteoporosis, fracture type, implant type, fracture reduction quality, early and late neck shaft angle (NSA), lag screw position in the femoral head, tip-apex distance (TAD), and cut-out. Fractures were classified according to the AO/OTA classification system, and the quality of fracture reduction was assessed using the Baumgaertner classification. The Cleveland method was used to record the location of the screw/blade within the head. Results: The study compared the implant features of four different PFN devices, including Double lag screw PFN, Wedge wing lag screw PFN nail, Helical blade PFN, and Integrated Dual Screw PFN. The statistical analysis indicated that early and late NSA, TAD, Reduction quality of fracture, Cleveland index, and the difference between PFN types were risk factors for Cut-out. ( P ≤ .001). Patients with helical blade PFN had a significantly higher rate of cut-out compared to other PFN devices. Univariate and multivariate regression analyses identified the Cleveland Index, fracture reduction quality ( P ≤ .001), TAD, and early and late NSA as significant predictors for cut-out complications ( P ≤ .001). Patients with poor Cleveland Index, poor fracture reduction quality, low TAD, and low NSA had a higher risk of cut-out ( P ≤ .001). Conclusion: In conclusion, careful consideration of patient and surgical factors, including implant design and placement, is crucial in minimizing the risk of complications such as cut-out.